Factors Influencing Hospitalization Expenses Among Patients with Lung Cancer in China - Tingting Xu; Nan Jiang; He Chen; Jun Feng; Qiming Feng; Xianjing Qin; Jinmin Zhao; Hongda Gao (SAGE Open)
Lung cancer poses a serious threat to human health. The direct medical expense and indirect social economic burden caused by high morbidity and poor prognosis rate of malignant tumor are higher than other diseases around the world, especially in some developing countries such as China. Guangxi is one of the less developed provinces in China and it is more essential to control the pressure on medical costs. We intend to explore influential factors of hospitalization expense for lung cancer and provide policy recommendations for the control of hospitalization expense. This study was divided into two aspects: internal and external analysis. Degree of structure variation (DSV) was used to explore internal factors. Generalized linear model (GLM) was used to explore external factor. Based on International Classification Diseases, 2,335 lung cancer patients were selected as studying objects. The total hospitalization expense in 2012 was the lowest, and then in increased from 2012 to 2015 year by year. Western medicine expense occupy the highest proportion in total hospitalization expense. Through the analysis of internal influencing factors, the medicine expense and examination expense have large contribution of structure variation from 2012 to 2016 based on DSV. For external factor, OR of occupation, medical insurance type, hospitalization frequency, and length of stay are statistically significant in GLM equation. The hospitalization expense is increasing and the effect of cost control is not significant. The study found that medicine expense and examination expense play an important role in controlling the total hospitalization expense. Therefore we can control the overall hospitalization expense increase by controlling these two expense items. Occupation, medical insurance type, hospitalization frequency, and length of stay have influence on hospitalization expense for lung cancer patients. Therefore we can also develop different cost control measures for different types of patients.